Avoiding Conflict: When Speaker Coordination Does Not Require Conceptual Agreement - Kabbach, Alexandre; Herbelot, Aurélie (Frontiers in Artificial Intelligence, 2021)
In this paper we discuss the socialization hypothesis—the idea that speakers of the same (linguistic) community should share similar concepts given that they are exposed to similar environments and operate in highly-coordinated social contexts—and challenge the fact that it is assumed to constitute a prerequisite to successful communication. We do so using distributional semantic models of meaning (DSMs) which create lexical representations via latent aggregation of co-occurrence information between words and contexts. We argue that DSMs constitute particularly adequate tools for exploring the socialization hypothesis given that 1) they provide full control over the notion of background environment, formally characterized as the training corpus from which distributional information is aggregated; and 2) their geometric structure allows for exploiting alignment-based similarity metrics to measure inter-subject alignment over an entire semantic space, rather than a set of limited entries. We propose to model coordination between two different DSMs trained on two distinct corpora as dimensionality selection over a dense matrix obtained via Singular Value Decomposition (SVD). This approximates an ad-hoc 16 coordination scenario between two speakers as the attempt to align their similarity ratings on a set of word pairs. Our results underline the specific way in which linguistic information is spread across singular vectors, and highlight the need to distinguish agreement from mere compatibility in alignment-based notions of conceptual similarity. Indeed, we show that compatibility emerges from idiosyncrasy so that the unique and distinctive aspects of speakers’ background experiences can actually facilitate—rather than impede—coordination and communication between them. We conclude that the socialization hypothesis may constitute an unnecessary prerequisite to successful communication and that, all things considered, communication is probably best formalized as the cooperative act of avoiding conflict, rather than maximizing agreement.